Penanaman Pendidikan Karakter untuk Anak Usia Dini - Mujiatun Mujiatun; Munafiah Munafiah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2020)
Character education has a higher meaning of moral education because it is not only teaching what is right and what is wrong but also helping children feel the good values, has willingness and ability to do so. The establishment of children’s personal character (character buildings) should start from the family as the children’s first interaction occurs within the family. Character education should be implemented since early childhood because it determines the children’s ability to develop their potentials. Character education in early childhood can lead children to be mature in processing their emotions. Emotional intelligence is an important provision in preparing early childhood to face future challenges, both in academic life and their life as citizen.